2009
DOI: 10.1016/j.susc.2008.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Interface and electronic characterization of thin epitaxial films

Abstract: a b s t r a c tThe interface and electronic structure of thin ($20-74 nm) Co 3 O 4 (1 1 0) epitaxial films grown by oxygenassisted molecular beam epitaxy on MgAl 2 O 4 (1 1 0) single crystal substrates have been investigated by means of real and reciprocal space techniques. As-grown film surfaces are found to be relatively disordered and exhibit an oblique low energy electron diffraction (LEED) pattern associated with the O-rich CoO 2 bulk termination of the (1 1 0) surface. Interface and bulk film structure a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 51 publications
8
61
2
Order By: Relevance
“…29,30 Co 3 O 4 films have been grown by post-oxidation, 17,31 atomic layer deposition (ALD), [32][33][34] chemical vapor deposition (CVD), [35][36][37][38] pulsed laser deposition (PLD), 18,39 and molecular beam epitaxy (MBE). [40][41][42] A number of substrates, including MgO, 18,34,36,38,39 39 Yttria-stabilized zirconia, 39 SiO 2 / Si, 32,33 and iridium 31 have been studied for the growth of crystalline Co 3 O 4 films. Among these substrates, spinel MgAl 2 O 4 (110) is an ideal substrate choice not only due to its small lattice mismatch with Co 3 O 4 (less than 0.05%) but also due to the fact that it is the only substrate thus far on which Co 3 O 4 preferentially grows (110)-oriented.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 Co 3 O 4 films have been grown by post-oxidation, 17,31 atomic layer deposition (ALD), [32][33][34] chemical vapor deposition (CVD), [35][36][37][38] pulsed laser deposition (PLD), 18,39 and molecular beam epitaxy (MBE). [40][41][42] A number of substrates, including MgO, 18,34,36,38,39 39 Yttria-stabilized zirconia, 39 SiO 2 / Si, 32,33 and iridium 31 have been studied for the growth of crystalline Co 3 O 4 films. Among these substrates, spinel MgAl 2 O 4 (110) is an ideal substrate choice not only due to its small lattice mismatch with Co 3 O 4 (less than 0.05%) but also due to the fact that it is the only substrate thus far on which Co 3 O 4 preferentially grows (110)-oriented.…”
Section: Introductionmentioning
confidence: 99%
“…Among these substrates, spinel MgAl 2 O 4 (110) is an ideal substrate choice not only due to its small lattice mismatch with Co 3 O 4 (less than 0.05%) but also due to the fact that it is the only substrate thus far on which Co 3 O 4 preferentially grows (110)-oriented. 41,42 MBE growth offers several advantages including precise control over flux and in situ analysis, but reports by Vaz et al have suggested that extensive post-growth ex situ annealing is required. 41,42 In this work, we report on thin MBE-grown Co 3 O 4 films on MgAl 2 O 4 substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22, with the substrate held at 570 K during growth. The high quality of the MgAl 2 O 4 (011) surface crystallinity was confirmed by LEED and RHEED, which display patterns characteristic of highly ordered surfaces, as shown in Fig.…”
Section: Sample Growthmentioning
confidence: 99%
“…These opportunities are a direct consequence of reduced dimensionality and/or interfacial phenomena from proximity effects between dissimilar materials Zubko et al (2011). Progress in growth techniques Chambers (2010); Eckstein & Bozovic (1995); Martin et al (2010); McKee et al (1998); Posadas et al (2007); Reiner et al (2009) ;Schlom et al (1992); Vaz et al (2009a); Vrejoiu et al (2008), nanoscale characterization tools Zhu (2005), and first principles calculations Cohen (2000); Fennie (2008); Picozzi & Ederer (2009); Rabe & Ghosez (2007); Spaldin & Pickett (2003); have been instrumental to our present ability to control matter down to the atomic scale and to fabricate nanoscale device structures with the potential for technological applications. Examples of current research work that aims at addressing some of the current grand challenges include the search for ultrasensitive sensors and actuators for applications in areas such as medicine and energy harvesting, the development of smaller and more energy efficient electronic devices that could replace current CMOS switches, and the design of intelligent systems that incorporate complex operations at the core processing level.…”
Section: Introductionmentioning
confidence: 99%